ERCP in patients with prior Billroth II gastrectomy: report of 30 years’ experience - Bove, Vincenzo; Tringali, Andrea; Familiari, Pietro; Gigante, Giovanni; Boškoski, Ivo; Perri, Vincenzo; Mutignani, Massimiliano; Costamagna, Guido (Endoscopy, 2015)
Background and study aim: Endoscopic retrograde cholangiopancreatography (ERCP) is difficult in patients with altered anatomy following Billroth II gastrectomy. Afferent loop intubation, selective cannulation, and sphincterotomy are the main issues. Experience from a tertiary referral endoscopy center is reported.Patients and methods: A total of 713 patients with Billroth II reconstruction who underwent ERCP between October 1982 and October 2012 were retrospectively identified from a prospectively collected database (mean age 69 ± 27 years; 567 males). The main indications for ERCP were common bile duct stones (51.2 %) and obstructive jaundice (24.8 %). Procedures were always started with a duodenoscope; in cases of failure to reach the papilla the duodenoscope was changed to a gastroscope. Endoscopic sphincterotomy was performed using a long-nose sigmoid inverted sphincterotome.Results: The successful duodenal intubation rate was 86.7 % (618/713 patients). The main reason for intubation failure was a long and angulated afferent loop. Successful cannulation/opacification of the desired biliopancreatic duct was 93.8 % (580/618). Biliary and/or pancreatic sphincterotomy were performed in 490 (84.5 %) and 23 (4.0 %) patients, respectively. The adverse event rate was 4.3 % (45/1050 procedures). Peritoneal perforation occurred in 1.8 % of the cases (19/1050 procedures) and always required immediate surgery. Two patients died after surgery (overall mortality 0.3 %). The other adverse events resolved following conservative management or endoscopic reintervention.Conclusions: In experienced centers, ERCP in Billroth II patients had morbidity and mortality rates that were comparable to patients with normal anatomy. The main reasons for failure were related to the inability to reach the papilla. Peritoneal perforation was the most common adverse event, and required a prompt surgical approach.